Survei Tingkat Kepuasan Member Terhadap Program Latihan dan Jasa Layanan Yang Diberikan Oleh Trainer di Queen Gym Sedayu Bantul Yogyakarta - Langgeng Pambudi; Ristanti Puji Astuti (CV Putra Publisher, 2023)
This research aims to determine member satisfaction with the training program and services provided by trainers at Queen Gym Sedayu Bantul Yogyakarta. Member satisfaction is related to consistency in training according to the program prepared by the personal trainer. The different training programs provided certainly affect the level of member satisfaction between one member and another. This type of research is quantitative. The population in this study were all members of Queen Gym who used personal trainers. The sample in this study was fitness members who used personal trainers at Queen Gym. The instrument used to measure the level of member satisfaction with training programs and services is a questionnaire. In this research, the data analysis technique uses descriptive statistical methods. The results of the study on member satisfaction with the training program and services provided by trainers as a whole were 56% satisfied. Based on each dimension, namely tangibles, 70% of members are satisfied, the reliability dimension is 54% satisfied, the responsiveness dimension is 68% of members are satisfied, the assurance dimension is 58% satisfied, and the empathy dimension is 58% of members are satisfied. satisfied. Thus, the level of member satisfaction with the training program and services provided by trainers at Queen Gym Sedayu Bantul Yogyakarta is in the satisfied category.